The nicotinic receptor drug sazetidine-A reduces alcohol consumption in mice without affecting concurrent nicotine consumption. (1st May 2018) - Touchette, Jillienne C.; Maertens, Jamie J.; Mason, Margaret M.; O'Rourke, Kyu Y.; Lee, Anna M.
Abstract: Alcohol and nicotine addiction are frequently co-morbid. The nicotinic acetylcholine receptors (nAChRs) are critical for both alcohol and nicotine addiction mechanisms, since nAChR drugs that reduce nicotine consumption have been shown to also reduce alcohol consumption. Sazetidine-A, a pre-clinical nAChR drug with agonist and desensitizing effects at α4β2 and α7 nAChRs, has been reported to reduce alcohol consumption and nicotine self-administration in rats when administered at high doses. However, this effect has not been replicated in mice. In this study, we examined the effect of sazetidine-A on alcohol and nicotine consumption in male and female mice utilizing voluntary oral consumption procedures previously developed in our lab. We found that sazetidine-A (1 mg/kg, i.p ) reduced overnight alcohol consumption, but did not affect nicotine consumption when presented either alone or concurrently with alcohol. Sazetidine-A did not reduce water or saccharin consumption at any dose tested. In a chronic co-consumption experiment in which either alcohol or nicotine was re-introduced after one week of forced abstinence, sazetidine-A attenuated post-abstinence consumption of alcohol but not nicotine. Sazetidine-A also significantly reduced alcohol consumption in an acute, binge drinking-in-the-dark procedure. Finally, we tested the effect of sazetidine-A on alcohol withdrawal, and found that sazetidine-A significantly reduced handling-induced convulsions during alcohol withdrawal. Collectively, these data suggest a novel role for the nAChR targets of sazetidine-A in specifically mediating alcohol consumption, separate from the involvement of nAChRs in mediating nicotine consumption. Delineation of this pathway may provide insight into novel therapies for the treatment of alcohol use disorders. Highlights: Sazetidine-A reduces alcohol but not concurrent nicotine consumption in mice. Sazetidine-A reduces only alcohol consumption after alcohol or nicotine abstinence. Sazetidine-A reduces binge, drinking-in-the dark alcohol consumption. Sazetidine-A does not affect water or sweet consumption at any dose tested. Sazetidine-A reduces handling-induced convulsions during alcohol withdrawal.